Combining Ability and Heterosis for Quantitative Characters III Sesame - Solanki, Z S; Gupta, Deepak (Annals of Arid Zone, 2016)
Line x tester analysis involving 10 female and 3 male lines from diverse origin revealed that additive gene action was predominant. Variety RT- I27, among the male parent. was the best general combiner for all the characters, except early flowering. Among the female parents, 51-718 for seed yield, EC-371832 for capsules per plant. ES-I-2-84 for IOOO-seed weight, EC-3518l9 for plant height and capsules bearing plant height, ES-123-1-84 for early maturity were the best general combiner. . The crosses EC-370823 x RT-127, EC-370663 x RT-I27, EC-351832 x RT-305 and SI-718 x RT-305 were the best for seed yield and its component characters. Hybridization systems, such as reciprocal recurrent crossing, which exploit both additive and nonadditive gene effects simultaneously, could be useful in the genetic improvement of the characters studied.